International agreements to reduce the crime of drug trafficking - Abdulilah Alshammri (الرافدین للحقوق)
The crime of drug trafficking has posed a serious challenge to the international community, and a threat that does not relate to the individual alone or to a specific society, but rather its humanitarian, social, economic, health and security impacts extend beyond all societies around the world.International law was keen to create an international legal system to control its production, distribution and consumption and to impose international restrictions to limit this phenomenon, especially during the first five decades of the twentieth century, to establish sound legal foundations for confronting drugs, but they were scattered and unconnected, and still needed efforts. Effective to put it into practice.